Production and characterization of laminated metal composite produced by cold roll bonding (Research, Society and Development, 2018)
The growing interest in the industries for laminated metal composite results in the needed to develop manufacturing technologies each time more efficiently. Ever since is a topic of a few discussion in Brazil and it results on the delay in scientific knowledge about the subject, the present work goals to produce a laminated metal composite by the cold roll bonding process in order to improve the national material competitiveness in the external marketplace. The first composite proposed was constitute by aluminium AA1050 and duplex stainless steel UNS S32304. Once the production attempts were ineffective, the second material replaced by a ferritic stainless steel AISI 430 in order to understand the bonding mechanism. The use of this metal allowed the laminated metal composite production and posterior study with peeling test, microestrutural analysis of the materials bonding mechanism.